PENGARUH ASAL BAHAN DAN MEDIA STEK TERHADAP KEBERHASILAN STEK PUCUK TEMBESU Fagraea fragrans (Roxb.) - Istomo Istomo; Atok Subiakto; Susilo Rahmadianto (Research Center for Biology-Indonesian Institute of Sciences, 2014)
Fagraea fragrans known as tembesu is a tree species used for panel wood (MDF, medium density fiberboard), particle board, veneer and furniture. The aim of this experiment was to know successful growth origin of shoot cutting F. fragrans and to study the effect of combination treatment the origin of cutting material and media F. fragrans. The shoot cutting was done with KOFFCO system. The results showedthat the cutting material from seedling juvenile shoot provided 61.56% of shoot formation, 91.42% of survivorship and 76.33% root formed.In addition, origin material from seedling juvenile gave a significantly effect on root length and wet root weight, wet shoot weight, dry root weight and significant on dry shoot weight parameter. The increasing age of the parent tree, diminishing cuttings success. The cuttings media cocopeat (coir dust) with paddy husk gives very significant effect on root length parameter, significant on wet root weight and gave very significant effect on root dry wet. There is an interaction between the cuttings material with cutting media, for root length parameter,wet root weight and dry root weight.